1973
DOI: 10.1172/jci107512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Splenectomy and Beta-Adrenoceptor Blockade on Cardiac Output Response to Acute Hypoxemia

Abstract: A B S T R A C T Acute hypoxemia produced by the inhalation of 8% and 5% oxygen increased cardiac output in intact anesthetized dogs by 38% and 62%, respectively. Although practolol, a cardioselective betaadrenergic blocking agent, reduced the increase in cardiac output in dogs subjected to severe hypoxemia (5% 02 breathing) from 62% to 43%, it only slightly reduced the cardiac output rise in dogs subjected to moderate hypoxemia (8% 02 breathing). Splenectomy, on the other hand, abolished the increase in cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Similarly, it decreases during severe hypoxia, probably a result of adrenergic stimulation (40). The increases in cardiac output and myocardial contractility during hypoxia probably are related to autoregulation ofthe peripheral vascular beds (41) and stimulation of the sympathetic nervous system (1,28,42,43). Results of the present study suggest that the systemic hemodynamic effects of hypoxia probably are not causally related to the accumulation of glycolytic metabolites or of other metabolites which are also affected by fluoroacetate.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, it decreases during severe hypoxia, probably a result of adrenergic stimulation (40). The increases in cardiac output and myocardial contractility during hypoxia probably are related to autoregulation ofthe peripheral vascular beds (41) and stimulation of the sympathetic nervous system (1,28,42,43). Results of the present study suggest that the systemic hemodynamic effects of hypoxia probably are not causally related to the accumulation of glycolytic metabolites or of other metabolites which are also affected by fluoroacetate.…”
Section: Resultsmentioning
confidence: 61%
“…Similarly, it is known that a shift from fatty acid oxidation to increased glycolysis occurs during hypoxia (22)(23)(24), probably partly because of the highly accelerated activity of phosphofructokinase (23) relative to that of thiokinase. However, neither total body nor myocardial oxygen consumption changes significantly in intact animals during mild to moderately severe hypoxia (25)(26)(27)(28), partly because the increased flow compensates for the reduction in arterial oxygen content (26). Likewise, oxygen consumption did not change after fluoroacetate administration in the present experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not investigate the possible role played by the spleen in augmenting the CO increase during hypoxia. Splenic contraction contributes to increased CO by increasing effective blood volume and cardiac filling pressures (Liang and Huckabee, 1973), but how this might have been altered by autonomic blockade was not evaluated. Histological evidence suggests that sympathetic terminals in the spleen may be more resistant to 60HDA than those in other tissues (Kostrzewa and Jacobowitz, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Recently one of us has demonstrated that this splenic substance plays an important role in regulating the cardiac output response to generalized hypoxia (12,13). The purpose of the present study was to inves tigate the possible role of myocardial adenylate cyclase-adenosine 3',5'-monophosphate (cyclic AMP) system in the cardiac output response to generalized hypoxemia.…”
mentioning
confidence: 94%